Search for CP violation in B0- B[bar]0 mixing using partial reconstruction of B0 → D*-Xl+[nu]l and a kaon tag - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review letters, 2013)
We present results of a search for CP violation in B0− ¯¯¯B0 mixing with the BABAR detector. We select a sample of B0→D*−Xℓ+ν decays with a partial reconstruction method and use kaon tagging to assess the flavor of the other B meson in the event. We determine the CP violating asymmetry ACP≡[N(B0B0)−N(¯¯¯B0¯¯¯B0)]/[N(B0B0)+N(¯¯¯B0¯¯¯B0)]=(0.06±0.17+0.38−0.32)%, corresponding to ΔCP=1−|q/p|=(0.29±0.84+1.88−1.61)×10−3.